Inhibition of dental plaque formation by toothpaste containing propolis - Nurin Aisyiyah Listyasari; Oedijani Santoso (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Plaque is the main cause of caries and periodontal disease. Caries and periodontal disease can be prevented by inhibiting dental plaque formation. To inhibit the formation of plaque, teeth must be brushed with toothpaste. According to previous studies, propolis contains apigenin and tt-farnesol classified as flavonoid that can inhibit the formation of dental plaque by inhibiting glucosyltransferase enzym and membrane integrity of Streptococcus mutans. Purpose: The aim of this study was to determine the effect of toothpaste containing propolis on the formation of dental plaque. Methods: Post test with only control group design was used. The subjects of this study were 30 boarding school students of Hidayatullah, Yayasan Al-Burhan, Gedawang, Semarang, divided into two groups, randomized control group and treatment group. Control group was not treated with toothpaste contanining propolis. Meanwhile, treatment group was treated with toothpaste containing propolis. Plaque then was measured by using plaque index of Sillness and Loe method after using toothpaste containing propolis for four hours. Afterwards, the data was analyzed by a computer program, Mann-Whitney test, with its significance p < 0.05. Results: The result of Mann-Whitney test showed a significant difference, 0.002 (p < 0.05), between the control group and the treatment group. The median of the control group was about 3.41, while that of the treatment group was about 0.58. Conclusion: The use of toothpaste contaning propolis can prevent dental plaque formation.Latar belakang: Plak merupakan penyebab utama terjadinya karies dan penyakit periodontal. Karies dan penyakit periodontal dapat dicegah dengan menghambat pembentukan plak gigi. Untuk mencegah terbentuknya plak, gigi harus digosok menggunakan pasta gigi. Penelitian terdahulu menyebutkan bahwa propolis mengandung flavonoid apigenin dan tt-farnesol yang mampu menghambat aktivitas enzim glukosiltransferase dan menghambat pembentukan membran bakteri Streptococcus mutans yang berperan pada pembentukan plak gigi. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pasta gigi dengan kandungan propolis terhadap pembentukan plak gigi. Metode: Menggunakan rancangan post test only control group design. Sampel penelitian ini adalah santri Pondok Pesantren Hidayatullah Yayasan Al-Burhan, Gedawang, Semarang, sebanyak 30 santri dibagi dalam dua kelompok secara acak yaitu kelompok kontrol diberikan pasta gigi tanpa kandungan propolis dan kelompok perlakuan diberikan pasta gigi dengan kandungan propolis. Plak diukur dengan menggunakan indeks plak menurut Sillness and Loe sesudah menggunakan pasta gigi dalam jangka waktu kurang lebih empat jam. Data diolah menggunakan program komputer dengan analisis statistik non parametrik Mann-Whitney dan taraf signifikansi diterima bila p < 0,05. Hasil: Analisis statistik non parametrik Mann-Whitney menghasilkan perbedaan rerata bermakna (p < 0,05) antara kelompok kontrol dan perlakuan sebesar 0,002. Nilai tengah skor plak pada kelompok kontrol sebesar 3,41 dan pada kelompok perlakuan sebesar 0,58. Kesimpulan: Penggunaan pasta gigi dengan kandungan propolis dapat menghambat pembentukan plak gigi.